Preparation of Pd Nanoparticles Stabilized by Modified Montmorillonite for Efficient Hydrodeoxygenation of Lignin-Derived Phenolic Compounds in Water - Wang, Xuerong; Li, Chi; Guo, Xinyuan; Wang, Zhichao; Cheng, Ruijing; Xu, Tianwei; Li, YiYing; Wang, Jinhui; Xu, Huanjun (Frontiers in Chemistry, 2022)
To develop a new and efficient catalytic route for the production of alkanes by upgrading the aqueous phenolic biofuels still remains a challenge. Here we designed and synthesized a bifunctional catalyst that used natural montmorillonite (MMT) as support and combined metal active sites and Brӧsted acid sites in the MMT via ion exchange and reduction roasting process. The catalytic activity of the as-synthesized Pd-MMT(H+) was evaluated by the hydrodeoxygenation (HDO) of a series of lignin-derived phenolic compounds in water. Our model reaction study reveals that the HDO of phenol undergo an initial hydrogenation of aromatic rings to produce cyclohexanol and cyclohexanone, followed by the dehydration of cyclohexanol to provide intermediate cyclohexene and a final hydrogenation of cyclohexene to afford cyclohexane product. The combination of high metal catalytic activity and Brӧsted acidity in Pd-MMT(H+) synergistically accelerated the HDO of phenol. Furthermore, good catalytic activity and recycle ability were also observed for other lignin-derived phenolic compounds.